Pengembangan Keahlian Wirausaha Siswa SMA melalui Pemahaman SMART Goal Setting - Mohamad Hadi Prasetyo (Harmoni Sosial : Jurnal Pengabdian dan Solidaritas Masyarakat, 2026)
This community service program aims to improve the entrepreneurial skills of high school students through the understanding and application of SMART Goal Setting. The activities were carried out in the form of workshops, group discussions, and intensive mentoring for eleventh-grade students. Data were collected through observations, short interviews, participant reflection notes, and documentation of business plans. Analysis was conducted using descriptive qualitative methods, emphasizing the participants' experience patterns and behavioral changes after participating in the program. The results showed that students were better able to formulate specific, measurable, realistic, relevant, and time-bound business goals. In addition, participants reported increased self-confidence, regularity in developing business steps, and awareness of the importance of structured planning. These findings confirm the relevance of implementing SMART Goal Setting in high school entrepreneurship education as a practical strategy that can support the emergence of aspiring young entrepreneurs.